Standard addition HPLC method for the determination of a-tocopherol in plasma samples of adolescent swimmers - Pistos, Constantinos M.; Vlachou, Myrsini; Theiakodimitri, Vassiliki; Philippou, Elena; Petrou, Michael; Middleton, Nicos; Panderi, Irene E.; Gkikas, Evangelos; Papoutsis, Ioannis I.; Spiliopoulou, Chara A.; Athanaselis, Sotiris A. (My University, 2014)
Vitamin E (a-tocopherol, a-Toc) has been widely used as a powerful antioxidant that protects against oxidation of cellular components. It is used to treat muscular dystrophies, menstrual cycle disorders, risks of pregnancy interruption and abnormalities of gonadal function in men. It is also used frequently from athletes as nutritional supplement for performance enhancing. A simple HPLC method has been validated for the determination of a-Toc in human plasma, using a Nova-Pack analytical column. The chromatographic run time was less than 12 minutes using a mobile phase of Acetonitrile-Methanol 85:15 (v/v), at 0.999 mL/min flow rate while UV/Vis detector was adjusted at 292 nm. The purpose of this study was to evaluate two different approaches for the construction of the calibration curve and further quantify samples from swimmer athletes in order to investigate potential quantification differences. It was shown that the existence of a-Toc as endogenous compounds might affect the actual concentrations and should be considered as an essential parameter during the development of a bioanalytical method for the determination of a-tocopherol in human plasma.
Keywords: A-tocopherol; HPLC; Plasma; Standard addition